Effect of Two Sudanese Cooking Methods on the Nutritional Value of Potato (Solanum tuberosum) Variety Draga - Elfaki, Ahmed E.; Abbsher, Afaf M. (University of Khartoum Journal of Agricultural Sciences, 2023)
This work was carried out to assess the nutritive value of draga variety of potato which was subjected to two cooking methods (boiling and frying). Proximate chemical analysis, minerals content, amino acids content and sensory evaluation were studied. Boiling resulted in insignificant decrease in protein, ash, fat and starch and increase in fibre and a significant decrease in total carbohydrates, while frying increased all tested components (protein, ash, fat, fibre, starch and total carbohydrates ). Generally, boiling and frying decreased significantly Na, K, P and Mg contents, while Fe was significantly increased. Ca was significantly increased by frying, while it was significantly decreased by boiling. The amino acids results showed that the two methods of cooking destructed phenylalanine, methionine, tyrosine and lysine. However, arginine was destructed by boiling only. Tryptophan recorded complete absence in all samples (raw, fried and boiled). Other amino acids (leucine, isoleucine, valine, histidine, aspartic acid, serine, glutamine and glycine) decreased by boiling and frying. Sensory evaluation revealed that there was no significant difference between the two methods of cooking with regard to texture and colour. However, flavour, taste and overall quality of fried potatoes were more acceptable than boiled ones.